1997
DOI: 10.1111/j.1540-8167.1997.tb01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Amiodarone Reduces Transmural Dispersion of Repolarization in the Canine Heart

Abstract: Our data demonstrate for the first time a direct effect of chronic amiodarone treatment to differentially alter the cellular electrophysiology of ventricular myocardium so as to produce an important decrease in transmural dispersion of repolarization, especially under conditions in which dispersion is exaggerated. These results may contribute to our understanding of the effectiveness of amiodarone in the treatment of life-threatening arrhythmias as well as to our understanding of the low incidence of proarrhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(103 citation statements)
references
References 49 publications
2
97
1
3
Order By: Relevance
“…In the case of quinidine, relatively low therapeutic levels of the drug (3 to 5 mol/L; 1.14 to 1.89 g/mL), produce a marked prolongation of the M-cell APD but not of epicardium and endocardium, consistent with a predominant effect of the drug to block I Kr at this concentration. 16 At higher concentrations (10 to 30 mol/L; 3.78 to 11.37 g/mL), quinidine produces a further prolongation of the EPI and endocardial action potential, consistent with an effect of the drug to block I Ks , and abbreviation of the APD of the M cell, because of its action to suppress late I Na . 17 Voltage clamp studies have shown that low concentrations of quinidine potently block I Kr but not I Ks , whereas higher concentrations potently block both I Kr and I Ks .…”
Section: Effect Of Cisapride In the Canine LV Wedge: Apd 90 Of M And mentioning
confidence: 95%
See 1 more Smart Citation
“…In the case of quinidine, relatively low therapeutic levels of the drug (3 to 5 mol/L; 1.14 to 1.89 g/mL), produce a marked prolongation of the M-cell APD but not of epicardium and endocardium, consistent with a predominant effect of the drug to block I Kr at this concentration. 16 At higher concentrations (10 to 30 mol/L; 3.78 to 11.37 g/mL), quinidine produces a further prolongation of the EPI and endocardial action potential, consistent with an effect of the drug to block I Ks , and abbreviation of the APD of the M cell, because of its action to suppress late I Na . 17 Voltage clamp studies have shown that low concentrations of quinidine potently block I Kr but not I Ks , whereas higher concentrations potently block both I Kr and I Ks .…”
Section: Effect Of Cisapride In the Canine LV Wedge: Apd 90 Of M And mentioning
confidence: 95%
“…When administered chronically, amiodarone produces a greater prolongation of action potential duration in epicardium and endocardium of the dog heart, but less of an increase, or even a decrease at slow rates, in the M region, thereby reducing TDR. 16 Chronic amiodarone therapy also suppresses the ability of the I Kr blocker D-sotalol to increase TDR or induce EADs. Similar results have recently been reported with chronic amiodarone in the chronic AV block dog model.…”
Section: Effect Of Cisapride In the Canine LV Wedge: Apd 90 Of M And mentioning
confidence: 99%
“…Our simulations also show that APD change in mid-myocardial-cells is the major contributor to the transmural APD dispersion, and hence, the tissue vulnerability. Although our models of Class III drug action on the virtual ventricular tissues are geometrically highly simplified, they reproduce relative changes of APD in endocardial, midmyocardial and epicardial tissue, and produce results consistent with a variety of experimental data [35][36][37]42].…”
Section: Discussionmentioning
confidence: 69%
“…Clinical trials on patients who already have had a myocardial infarct (damage to heart muscle following a heart attack) have shown that amiodarone has fewer pro-arrhythmic side effects than d-sotalol. The effects of amiodarone and d-sotalol are incorporated in the model as changes in the density of I Kr (µA/µF) -the primary target for Class III drug action -and the slow L-type calcium current I Ca,L (µA/µF), which reproduce relative alterations of APD in the three tissue types [35][36][37]. For the d-sotalol model I Kr is depressed by 40% in the endo-, by 100% in M-cell, and by 65% in the epicardial, regions; for the amiodarone model I Kr is uniformly depressed by 50% throughout the wall and I Ca,L is depressed by 40% in the M-cells.…”
Section: Constructing Virtual Ventricular Tissuementioning
confidence: 99%
“…The decrease in the transmural dispersion of ventricular repolarization and the consequent inhibition of the development of early afterdepolarization can possibly Ž . explain this effect of amiodarone Sicouri et al, 1997 . Class IrB antiarrhythmics may reduce the occurrence of Ž this arrhythmia.…”
Section: Discussionmentioning
confidence: 99%